Regulating Current Strength Using A Rheostat In The Conditions Of Digitalization - S.G.Kaypnazarov (Zien Journals, 2025)
Today, the issue of improving the digital literacy of the population is being actively raised. This primarily concerns pupils, who have the highest demand for the use of digital technologies and internet capabilities in learning and everyday life. Pupils who develop digital literacy as an integral part of their education are more effective in their studies and are more in demand when it comes to employment.
Keywords: digitalization of education; digital virtual laboratory